Insignificant effects of eddies and typhoons on the biogeochemistry of the tropical northwest Pacific Ocean - Seo, Junhyeong; Hahm, Doshik; Kim, Guebuem; Lee, Inhee; Park, Jihyun; Na, Taehee; Park, Jae-Hyoung; Kang, Sok Kuh; Hwang, Jeomshik (Frontiers in Marine Science, 2022)
We investigated the effects of eddies and typhoons on the biogeochemistry of the tropical northwest Pacific by examining the distribution of nutrients, dissolved oxygen (DO), chlorophyll-a (Chl-a), gross primary production (GPP), dissolved organic carbon (DOC), and fluorescent dissolved organic matter (FDOM). Water samples were collected from anticyclonic and cyclonic eddies in September 2019 and 2020, and before and after the passage of a Category 2 typhoon in 2019. The study region was characterized by a deep nitracline ( 150 m), which was deeper than both the pycnocline ( 50 m) and the FDOM-depleted layer ( 75 m). A subsurface chlorophyll maximum layer was observed at 100–150 m depth. No clear differences in Chl-a, DO, GPP, DOC, and FDOM were observed for the anticyclonic and cyclonic eddies, indicating that the eddies did not have a significant influence on biological production. Similarly, there were no discernable changes in Chl-a concentrations or other biogeochemical parameters after the passage of the typhoon, which induced water mixing to a depth of 60 m. We conjecture that the nutrient-depleted layer was too deep for any eddy- or typhoon-induced vertical mixing to cause upwelling of nutrients to the euphotic zone. Our results imply that the disturbances caused by mesoscale processes in the upper layer of the highly oligotrophic northwest Pacific may have a smaller effect than in oceans in other parts of the world.